Dravet Variant SCN1AA1783V Impairs Interneuron Firing Predominantly by Altered Channel Activation - Layer, Nikolas; Sonnenberg, Lukas; Pardo González, Emilio; Benda, Jan; Hedrich, Ulrike B. S.; Lerche, Holger; Koch, Henner; Wuttke, Thomas V. (Frontiers in Cellular Neuroscience, 2021)
Dravet syndrome (DS) is a developmental epileptic encephalopathy mainly caused by functional NaV1.1 haploinsufficiency in inhibitory interneurons. Recently, a new conditional mouse model expressing the recurrent human p.(Ala1783Val) missense variant has become available. Here we provide an electrophysiological characterization of this variant in tsA201 cells, revealing both altered voltage-dependence of activation and slow inactivation without reduced sodium peak current density. Based on these data, simulated interneuron (IN) firing properties in a conductance-based single-compartment model suggested surprisingly similar firing deficits for NaV1.1A1783V and full haploinsufficiency as caused by heterozygous truncation variants. Impaired NaV1.1A1783V channel activation was predicted to have a significantly larger impact on channel function than altered slow inactivation and is therefore proposed as the main mechanism underlying IN dysfunction. The computational model was validated in cortical organotypic slice cultures derived from conditional Scn1aA1783V mice. Pan-neuronal activation of the p.Ala1783V in vitro confirmed a predicted IN firing deficit and revealed an accompanying reduction of interneuronal input resistance while demonstrating normal excitability of pyramidal neurons. Altered input resistance was fed back into the model for further refinement. Taken together these data demonstrate that primary LOF gating properties accompanied by altered membrane characteristics may match effects of full haploinsufficiency on neuronal level despite maintained physiological peak current density, thereby causing DS.